The Importance of Being Wanted - Do, Quy-Toan; Phung, Tung D. (2012)
We identify birth wantedness as a source of better child outcomes. In Vietnam, the year of birth is widely believed to determine success. As a result, cohorts born in auspicious years are 12 percent larger. Comparing siblings with one another, those of auspicious cohorts are found to have two extra months of schooling. The Vietnamese horoscope being gender-specific, this difference will be shown to be driven by birth planning. Children born in auspicious years are more likely to have been planned, thus benefitting from a more favorable growth environment.